2011
DOI: 10.1186/cc10455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid loading during hypovolaemic shock on caspofungin pharmacokinetic parameters in pig

Abstract: IntroductionCaspofungin treatment is frequently initiated in shock patients. In the present study, we investigated the influence of hypovolaemic shock requiring fluid loading on the plasma and pulmonary pharmacokinetic parameters of caspofungin in the pig.MethodsAfter being anaesthetised and mechanically ventilated, 12 pigs were bled to induce a two-hour deep shock and resuscitated using normal saline based on haemodynamic goals. A one-hour infusion of 70 mg of caspofungin was started at the beginning of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous research reported that patients experienced various degrees of hypoproteinemia; however, the albumin concentrations were all normal in the patients included in the present study. In addition, as a hydrophilic drug, the V of caspofungin can be significantly increased by fluid shifts and large‐volume fluid resuscitation ( 28 ); these methods are common in critically ill patients. When hypoalbuminemia occurs, the circulating blood volume is more likely to transfer to the third space, leading to a more significant increase in the V of caspofungin ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that patients experienced various degrees of hypoproteinemia; however, the albumin concentrations were all normal in the patients included in the present study. In addition, as a hydrophilic drug, the V of caspofungin can be significantly increased by fluid shifts and large‐volume fluid resuscitation ( 28 ); these methods are common in critically ill patients. When hypoalbuminemia occurs, the circulating blood volume is more likely to transfer to the third space, leading to a more significant increase in the V of caspofungin ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with normal liver and kidney function, hypoalbuminemia can result in elevated levels of unbound drugs, potentially leading to an increased CL, especially in highly protein-bound antibiotics like caspofungin. Additionally, as a hydrophilic drug, caspofungin’s V d may increase due to fluid shifts and extensive fluid resuscitation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%